Concept and measurement of interests - Bawa, Surinderjit Kaur. (New Delhi : Deep & Deep, 1995)
Mainly focussed on the area of comparative study of various types of interests of adolescents of different geographical regions of Punjab, India.
Includes bibliographical references (p. [209]-215) and index.
Keywords: Teenagers -- India -- Social conditions; Behavior modification -- India; Adolescent psychology -- India